Cytomegalovirus-induced hepatitis in children - L.A. Khodak; V.I. Brailko; N.G. Dejneka (Zaslavsky O.Yu., 2018)
The article presents analysis of the structure of viral hepatitis in children, among whom cytomegalovirus (СMV)-induced hepatitis as mono-infection was diagnosed in 8 (3.4 %) patients, mixed infection - in 10 (4.3 %). Clinical observations of СMV-induced hepatitis in children of different ages are represented that shows different variants of its course: acute СMV-induced hepatitis, which resulted in recovery in a 12-year-old child, and primary chronic one in a 5-month-old child.